Analisis Kinerja Petugas Penyuluh Lapangan Keluarga Berencana (PLKB) Di Kecamatan Polinggona Kabupaten Kolaka - Jaya, Ansar; Amir, Muh; Abdullah, Muhammad Zein (REZ PUBLICA, 2020)
The purpose of this research is to find out and explain the Performance of Family Planning Field Extension Workers in Polinggona Subdistrict, Kolaka Regency and To find out the factors that influence the Performance of Family Planning Field Extension Workers in Polinggona District, Kolaka District. Data collection techniques carried out by library research and field research, while data analysis techniques used descriptive qualitative analysis techniques. The results of this study indicate that the documentation and interview observation techniques carried out at Polinggona District on Analysis of the performance of family planning counselors can be concluded that the performance of family planning counselors has been running quite well in terms of quality and quantity which shows that the performance of the The family planning field counselor has carried out his duties ranging from counseling to evaluation can be proven from interview quotes, from several informants, documentation and from relevant data. Then there are still several factors that inhibit the occurrence of counseling including inadequate facilities and infrastructure, as well as human resources that are still less skilled due to the lack of training provided. Then it can be concluded that the Performance of Family Planning Field Extension has been going quite well.